The development of ability emotional intelligence during adolescence - Megías-Robles, Alberto; Gutiérrez-Cobo, María José; Fernández-Berrocal, Pablo; Gómez-Leal, Raquel; Cabello-González, Rosario (Elsevier, 2024)
This study aimed to examine the development of ability emotional intelligence (EI) in the adolescent population with a Spanish performance-based instrument of EI: Botín Foundation's Emotional Intelligence Test for Adolescents (TIEFBA), which assesses the respondent's ability to solve emotional problems for each of the four emotional skills of the Mayer and Salovey EI model. With a large cross-sectional sample of Spanish adolescents (N = 5377; girls, 50.9 %) aged from 10 to 17 years (M = 13.57), the authors examined the progression of ability EI across the adolescent period, as well as the effects of gender. The results revealed that girls scored higher than boys on both the total EI and its four branches. Moreover, total EI increased throughout adolescence, but only in girls. Regarding EI branches, while using and understanding emotions increased with age in both girls and boys, managing emotions increased only in girls and perceiving emotions decreased in boys. These findings represent a significant advance that helps us define the evolution of emotional skills in adolescence, providing empirical support for using this performance measure of ability EI.
Keywords: Psicología; Adolescentes - Psicología; Emotional intelligence; Adolescence; Gender; Age